The price of hesitation: How the climate crisis threatens price stability and what the ECB must do about it - Yannis Dafermos; Alexander Kriwoluzky; Mauricio Vargas; Ulrich Volz; Jana Wittich (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This report presents for the first time empirical evidence of the impact of nat-ural disasters on inflation in the eurozone, highlighting the challenges facing the ECB to achieve price stability in the era of the climate crisis. Our results show that natural disasters lead to increases in headline and core inflation, with price increases being higher for food and beverages. The effects are small but significant. We also show that there are significant differences between euro-zone countries in the way that inflation is affected by natural disasters. With an escalation of the climate crisis, the frequency and intensity of climate-related hazards will increase in the eurozone. If past data shows that natural events have already an impact on inflation, this effect can only become stronger as global warming increases, with important ramifications for the ECB's policies and operations. The ability of the ECB to control inflation may be significantly undermined if the world passes the 1.5 or 2 degrees threshold. Therefore, actions that prevent an increase in global warming have an im-portant role to play in allowing the ECB to achieve its primary objective in the future. The ECB has taken an important step by announcing its new monetary strategy and climate action plan. While this is a critical first move in the right direction, the ECB climate action plan falls short of providing an ambitious agenda con-sistent with the climate emergency that we are facing. [...]
Additional information: Final report on behalf of Greenpeace Germany.
Keywords: 330